Manual de procesos y procedimientos para el control interno en el área de compras bajo la metodología coso I para la empresa Anton Bistró - Cuenca Vidarte, Marcela (Universidad Antonio Nariño, 2023)
The changes that have occurred in the business environment have forced companies to develop control strategies that allow obtaining favorable results in the development of their operations, as is the case of the company ANTON BISTRO, which requires a design to internal control in the purchasing area, Internal control in a company aims to measure efficiency and productivity to achieve time optimization, especially if it focuses on the basic activities that they perform, it is a plan of techniques and procedures where all the administrative and accounting measures of the company will be foreseen.